Political Betrayal of Education - Rifqah Ramadhana Jufri; Andi Neneng Nurfauziah; Herwanita Herwanita (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The deteriorating practice of scientific elaboration in education is often associated with the increasing information overload in the digital social space. This condition not only impacts the quality of knowledge production but also weakens individuals' reflective capacity to interpret their roles and the educational ecosystem. In this context, educational actors tend to be mired in ambivalence, on the one hand as actors, but on the other as victims of malpractice, related information, and increasingly problematic educational political policies. Hence, the author conceived the research title